2014
DOI: 10.1021/ie501248y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Preparation of Acid-Stable and High Dehydration Performance Mordenite Membranes

Abstract: Highly intergrown mordenite membranes were rapidly prepared on seeded aluminum supports by microwaveassisted synthesis. Both the thicknesses of the zeolite layer and the sizes of the zeolite crystals of the mordenite membranes were highly dependent on the synthesis time. With a SiO 2 :0.08Al 2 O 3 :0.2Na 2 O:0.1NaF:35H 2 O precursor synthesis gel, a compact and 0.75 μm thick mordenite crystal layer was successfully prepared on the aluminum support at 170 °C for 3 h. The as-synthesized mordenite membrane exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Thus, a similar phenomenon may have taken place in this study. However, compared with a conventional study tested in a similar testing condition of 90:10 wt % CH 3 COOH/water mixture at 348 K, the permeability of MOR-type zeolite membrane decreased to nearly half after 30 h of PV test [11] while the developed h-WO 3 membrane decreased by only 20% and stabilized. This implies that the plugging of h-WO 3 pores caused by the CH 3 COOH molecule was much less compared to the mordenite pores.…”
Section: Pv Performancementioning
confidence: 56%
See 1 more Smart Citation
“…Thus, a similar phenomenon may have taken place in this study. However, compared with a conventional study tested in a similar testing condition of 90:10 wt % CH 3 COOH/water mixture at 348 K, the permeability of MOR-type zeolite membrane decreased to nearly half after 30 h of PV test [11] while the developed h-WO 3 membrane decreased by only 20% and stabilized. This implies that the plugging of h-WO 3 pores caused by the CH 3 COOH molecule was much less compared to the mordenite pores.…”
Section: Pv Performancementioning
confidence: 56%
“…Both water and CH3COOH permeance decreased by about 20% from the first test to the second test; however, the permeance was still high compared to our previous report [26] and maintained nearly constant thereafter for more than 300 h. This indicated that the h-WO3 membrane is durable against acidic solvents and that its performance can be maintained even during a long-term-separation test. So far, several zeolite membranes have been evaluated using long-term separation tests [10][11][12][13]15,17]. The initial decrease in permeability has been observed in almost all cases.…”
Section: Pv Performancementioning
confidence: 99%
“…The key point of the synthesis method was blending the base polymer (PVDF) with its derivatives and tailoring the membrane casting conditions . The same copolymer blended with PVDF has been used to produce a series of novel pHsensitive microfiltration membranes via ultraviolet irradiation-induced atom transfer radical polymerization (Hua et al, 2014). This "grafting from" approach provides the control growth of the polymer chains from the membrane surface.…”
Section: Formation Of Ph-responsive Membranesmentioning
confidence: 99%
“…Separation of oil and water from stable oil/water emulsions is very challenging because of the sub-micrometer size of the oil droplets. Conventional oily wastewater treatment processes such as gravity separation, coagulation, thermal deemulsification, free-floating oil, flocculation, and biological treatments show very poor removal of low oil concentrations (Zhu et al, 2014). Among the existing oil/ water separation membranes, hydrophilic membranes exhibited the most effective fouling resistance behavior.…”
Section: Oil/water Separationmentioning
confidence: 99%
“…0.27 kg•m −2 •h −1 . Zhu et al [103] reported a high-silica ZSM-5 membrane, which has been proven to be stable in 90 wt% HAc/H 2 O mixture dehydration at 75°C for 60 days. All these results indicated that improving the Si/Al ratio in the framework would be helpful for improving the stability of zeolite membranes.…”
Section: Stabilities Of Hydrophilic Zeolite Membranesmentioning
confidence: 99%